Mass Transfer During Osmotic Dehydration of Banana (Dwarf Cavendish) Slices - Kar, Abhijit; Chandra, Pitam; Parsad, Rajender; Dash, Sanjaya K (Journal of Agricultural Engineering, 2005)
Mass transfer during osmotic dehydration of banana has been studied with respect to the solution concentration (30 - 70degree Brix), temperature (25 - 65degree C) and solution to sample ratio (1-9). The diffusion coefficients have been calculated using the sorption data by a method of successive approximations. The diffusion coefficient has been empirically correlated with the process variables and a high degree of correlation (RÂ² =0.91) was observed between predicted and experimental values. The solution of Fick’s Law for unstady state mass transfer in a plane sheet has been used to predict the moisture ratios over the entire experimental range. The error between the observed and the predicted values of moisture ratios was less than 10% indicating the adequacy of diffusion coefficient estimation.